An exploration of LAF‐bTMB as a predictor for the efficacy of immunotherapy combined with chemotherapy in non—small cell lung cancer - Shuyang Zhang; Lu Yang; Yaning Yang; Ying Xin; Yan Wang (Thoracic Cancer, 2022)
Abstract Background Immune checkpoint inhibitor (ICI) combined with chemotherapy is one of the standards of care for advanced non–small cell lung cancer (NSCLC) without driver mutations. However, the biomarker of combination therapy is still unknown. Although previous studies have confirmed that low allele frequency adjusted blood‐based tumor mutational burden (LAF‐bTMB) is associated with the efficacy of ICI monotherapy, there has been no report on the correlation between the efficacy of LAF‐bTMB and ICI combined chemotherapy. This study aimed to explore whether LAF‐bTMB can be used as a predictive biomarker for the efficacy of immunotherapy combined with chemotherapy in advanced NSCLC. Methods This study enrolled patients diagnosed with advanced NSCLC and who received ICI combined with chemotherapy for first‐line therapy from May 2020 to December 2021 at Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College. Clinical information, treatment information, survival data, and peripheral blood samples of every patient before treatment were collected. Next‐generation sequencing was performed on plasma samples to estimate bTMB and LAF‐bTMB. Results A total of 42 patients with NSCLC were enrolled. In this cohort, 19 patients achieved partial response (PR), and the objective response rate (ORR) was 45.2%. The median progression‐free survival (PFS) of all patients was 13.4 months (95% CI, 7.49–19.72). Both PFS and the overall survival (OS) were significantly longer in the responder (R) group than in the non‐responder (NR) group (median PFS, 16.4 months vs. 7.2 months, p = 0.028; median OS, NE vs. 9.3 months, p = 0.016). There was no significant difference in bTMB and LAF‐BTMB between the R and NR group. The ORR of patients with LAF‐bTMB≤8muts/Mb was significantly higher than that of patients with LAF‐bTMB >8muts/Mb (ORR, 61% vs. 26%, respectively, p = 0.033). When LAF‐bTMB ≤8muts/Mb or > 20muts/Mb, ORR was significantly higher than that of patients with LAF‐bTMB between 8 and 20muts/Mb (ORR were 57% and 21%, p = 0.047). No correlation has been found between LAF‐bTMB and PFS or OS. Conclusions This study confirmed that neither bTMB nor LAF‐bTMB is feasible as a potential predictor of first‐line immunochemotherapy for advanced NSCLC. More suitable biomarkers need to be explored to screen patients with better efficacy of immunotherapy combined with chemotherapy in the future.